The Death of Narcissus: On Musical Subjectivity - Currie, James (Revista Vórtex, 2013)
On the first page of the preface to Michael Steinberg’s excellent book, Listening to Reason: Culture, Subjectivity, and Nineteenth-Century Music, the author states that the book’s origin can be located specifically to "August 1990," when he was giving "a short preconcert lecture on Brahms at the first Bard Music Festival."